Semiconductor devices : Physics and technology - Sze, S. M. (New Delhi: Wiley India, 2002)
This book is an introduction to the physical principles of modern semiconductor devices and their advanced fabrication technology. It begins with a brief historical review of major devices and key technologies and is then divided into three sections: semiconductor material properties, physics of semiconductor devices and processing technology to fabricate these semiconductor devices
Appendices A-L 531-550p.; Index 551-564p.
Keywords: Devices; Physics; Semiconductor Devices; General Science